Proximal Femoral Nail vs. Dynamic Hip Screw in Treatment of Intertrochanteric Fractures: A Meta-Analysis - Zhang, Kairui (International Scientific Literature, Inc., 2014)
BACKGROUND: The aim of this meta-analysis was to compare the outcomes of proximal femoral nail (PFN) and dynamic hip screw (DHS) in treatment of intertrochanteric fractures. MATERIAL/METHODS: Relevant randomized or quasi-randomized controlled studies comparing the effects of PFN and DHS were searched for following the requirements of the Cochrane Library Handbook. Six eligible studies involving 669 fractures were included. Their methodological quality was assessed and data were extracted independently for meta-analysis. RESULTS: The results showed that the PFN group had significantly less operative time (WMD: −21.15, 95% CI: −34.91 – −7.39, P=0.003), intraoperative blood loss (WMD: −139.81, 95% CI: −210.39 – −69.22, P=0.0001), and length of incision (WMD: −6.97, 95% CI: −9.19 – −4.74, P<0.00001) than the DHS group. No significant differences were found between the 2 groups regarding postoperative infection rate, lag screw cut-out rate, or reoperation rate. CONCLUSIONS: The current evidence indicates that PFN may be a better choice than DHS in the treatment of intertrochanteric fractures.